REIMAGINING FOREIGN LANGUAGE EDUCATION: INTEGRATING LINGUOCULTURAL COMPETENCE THROUGH ENGLISH AND UZBEK ONOMASTIC VOCABULARY - Mamatkulova Bakhtijon Ravshanovna (International Journal of Literature and Language Studies, 2026)
The rapid development of globalization has transformed foreign language education by emphasizing not only linguistic proficiency but also intercultural and linguocultural competence. Proper names, as an essential component of language, represent valuable cultural symbols reflecting the historical, social, and national identity of a community. However, onomastic vocabulary is often insufficiently addressed in English language instruction, limiting learners’ ability to interpret authentic texts and communicate effectively across cultures. This study investigates the integration of English and Uzbek onomastic vocabulary into foreign language teaching through a linguocultural framework. Using comparative, descriptive, and pedagogical approaches, the research proposes an instructional model that combines cultural interpretation with communicative language teaching. The findings suggest that integrating onomastic vocabulary into classroom practice enhances intercultural awareness, vocabulary retention, critical thinking, and communicative competence. The study offers methodological recommendations for English language educators seeking to modernize foreign language instruction in multilingual educational settings.